PENGARUH GAYA KEPEMIMPINAN, KOMUNIKASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA PENGURUS (Studi kasus PMII Rayon Al-Farabi) - Ali Imron Maulana; Budi Wahono; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis study is entitled The Effect of Leadership Style, Communication, and Organizational Commitment on Management Performance (PMII Rayon Al-Farabi case study). The purpose of this determination is to find out and analyze the influence of leadership style, communication, and organizational commitment to the management performance, both simultaneously and partially. Managing people in PMII Rayon Al-Farabi's organization is not easy, because it has a board of 225 people. Of course they have varied and different characters, desires, thought patterns, and skills. So that it becomes an important capital for management and organizational leaders to have an ideal leadership style, good communication and strong commitment, so that each individual has a real contribution and good performance. This type of research used in this research is quantitative research. Analysis technique using multiple regression. While the sampling technique in this study uses proportionate stratified rondom sampling. Based on the results of this study that the leadership style (X1), communication (X2), and organizational commitment (X3) simultaneously have an influence on performance (Y). The independent variable that has a dominant influence is communication (X2), which has a positive and significant effect on the performance of the board. Keywords: Leadership Style, communication, organizational commitment, performance